An Analysis of IELTS-Based Literacy Levels: A Case Study at the First Semester Students of FBIB Unisbank Semarang - Sugeng Purwanto (Dinamika Bahasa dan Budaya, 2008)
The study is aimed at describing the levels of literacy on the basis of IELTS’ standards of competencies. It is a case study at the first Semester Students of FBIB, Unisbank of 2007/2008 academic year. In the study, twenty students were randomly selected out of total number of students consisting both Diploma and Undergraduate Study Programs. The data were collected by administering IELTS test to those selected students of which the test results were matched against predetermined criteria for literacy levels (Hammond 1992) in order to classify them into the appropriate levels of literacy. The study indicates that all students (100%) were of the performative level of literacy with respect to the overall IELTS scores. Only 25% of the students managed to get informative level in speaking subtest and 20% in reading subtest. It is therefore recommended that literacy education be integrated in the curriculum of FBIB Unisbank, Semarang.   Key Words: Literacy, IELTS